An improved method for introducing site-directed point mutation into the Toxoplasma gondii genome using CRISPR/Cas9. Issue 5 (October 2016) - Sugi, Tatsuki; Kato, Kentaro; Weiss, Louis M.
Abstract: Toxoplasma gondii is an obligate intracellular parasite in the phylum Apicomplexa. Due to the ease of genetic manipulations in T. gondii it serves as a model organism for intracellular parasites. We utilized CRISPR/Cas9, which can be designed to target a specific genomic locus, to introduce site-directed point mutations directly into the T. gondii genomes. This paper contains step-by-step protocols for: (1) designing the guide RNA sequence; (2) constructing the CRISPR/Cas9 construct for a target gene and preparing a donor sequence; and (3) transfecting the CRISPR/Cas9 modules into the parasite and selecting the parasite with the desired point mutation. In brief: T. gondii strains PRU∆ ku80 ∆ hxgprt or RH∆ ku80 ∆ hxgprt were nucleofected with pDHFR-SAG1::Cas9-U6::sgGeneA and a mutation donor sequence at a molar ratio of ~ 1:3. After 10 days of 1 μM pyrimethamine selection the parasite population was enriched for parasites with the desired point mutation. This technique was also applied to evaluate the importance of genes of interest by introducing either knock out or silence mutations at the same time and then tracking the population kinetics of the resultant T. gondii strains. In addition to previously established high efficient knock out and knock in strategies in Toxoplasma, the site directed point mutation technique presented in this manuscript provides another powerful tool set for T. gondii research. Highlights: CRISPR/Cas9 makes it possible to introduce point mutation(s)into the Toxoplasma gondii genome. A point mutation can be introduced without inserting the selectable marker into the gene locus. Drug selection with a marker on the Cas9 construct enriched transgenic parasites. A competitive assay herein provides a quick evaluation of the effects of a target 2gene mutation on population dynamics.